2003
DOI: 10.1359/jbmr.2003.18.4.784
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Disease Conditions, Bone Mineral Density, and Prevalent Vertebral Deformities in Men and Women 50 Years of Age and Older: Cross-Sectional Results From the Canadian Multicentre Osteoporosis Study

Abstract: This cross-sectional cohort study of 5566 women and 2187 men 50 years of age and older in the population-based Canadian Multicentre Osteoporosis Study was conducted to determine whether reported past diseases are associated with bone mineral density or prevalent vertebral deformities. We examined 12 self-reported disease conditions including diabetes mellitus (types 1 or 2), nephrolithiasis, hypertension, heart attack, rheumatoid arthritis, thyroid disease, breast cancer, inflammatory bowel disease, neuromuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
3
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 25 publications
9
79
3
1
Order By: Relevance
“…(16,18,20) Our data are in agreement with those from the Canadian Multicentre Osteoporosis Study, which found no evidence of an increase in the prevalence of vertebral fractures in T2DM men aged 50 years and older (adjusted OR, 0.77; 95% CI, 0.49 to 1.22). (16) Another group reported that the presence of T2DM was an independent risk factor for prevalent VFs in Japanese men aged 50 years and older (OR, 4.73; 95% CI, 2.19 to 10.2) after adjusting for age, BMI, and lumbar spine BMD. (20) Because VFs are a major cause of pain and disability, (36,37) it is important to identify subjects at increased risk of VFs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(16,18,20) Our data are in agreement with those from the Canadian Multicentre Osteoporosis Study, which found no evidence of an increase in the prevalence of vertebral fractures in T2DM men aged 50 years and older (adjusted OR, 0.77; 95% CI, 0.49 to 1.22). (16) Another group reported that the presence of T2DM was an independent risk factor for prevalent VFs in Japanese men aged 50 years and older (OR, 4.73; 95% CI, 2.19 to 10.2) after adjusting for age, BMI, and lumbar spine BMD. (20) Because VFs are a major cause of pain and disability, (36,37) it is important to identify subjects at increased risk of VFs.…”
Section: Discussionsupporting
confidence: 89%
“…(6,15,16) To date, information on VF risk in T2DM men is very limited and conflicting, and mostly based on prevalent VFs. (16)(17)(18)(19)(20) Thus, it is still not clear whether VF risk is increased in men with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Although adjustment for adiposity weakened the association, it did not remove it completely. The main strength of this study, and an advance over previous studies [6,7] was the measurement of insulin levels in the cohort; hyperinsulinaemia can affect BMD both directly and indirectly (acting through BMI), and our results would support the latter hypothesis.…”
Section: Discussionsupporting
confidence: 56%
“…A recent cross-sectional study of over 7500 Canadian men and women showed that type 2 diabetes was associated with higher bone mineral density (BMD) even after adjustment for confounding variables, although relationships were stronger in women [7]. The authors speculated that these findings might be due to an anabolic effect of insulin on bone tissue, as type 2 diabetes may be preceded by a period of insulin resistance leading to hyperinsulinaemia.…”
Section: Introductionmentioning
confidence: 99%
“…The association between low bone mineral density (BMD) and diabetes has most consistently been observed in type 1 patients [4,5], with increased bone mineral loss attributed to early age at diagnosis, long duration, prolonged poor glycaemic control and high insulin doses [6][7][8][9]. In type 2 diabetes, the relationship is less clear, with reports of increased [10], decreased [11] or unchanged [12] bone mass and BMD, probably reflecting the heterogeneity of the disease and/or the different study methodologies used.…”
Section: Introductionmentioning
confidence: 99%